Photo- and Electrochemical Organic Transformations Involving Radical Pathway: A Retrospection of Our Green-Chemistry-Inspired Synthetic Endeavours - Brahmachari, Goutam (Synlett, 2024)
This account summarises our recent efforts (2020 to mid-2024) in designing and developing a handful of promising organic transformations for accessing several diversely functionalized biologically relevant organic scaffolds by following the green-chemistry principles with a particular focus on the application of low-energy visible light and electrochemistry. Mechanistic studies of each of these reactions established the involvement of a radical pathway.1 Introduction2 Green-Inspired Organic Transformations2.1 Visible-Light-Driven Organic Synthesis2.1.1 Synthesis of Functionalized Dihydrofuro[3,2-c]chromenones2.1.2 Synthesis of Functionalized 2-(Aryl/alkylamino)-3-(aryl/alkylselanyl)naphthalene-1,4-diones and 2-(Arylamino)-3-(arylthio)naphthalene-1,4-diones2.1.3 Synthesis of Functionalized 6-(Arylthio/arylseleno)benzo[a]phenazin-5-ols2.1.4 Synthesis of Functionalized 3-(Alkyl/benzylthio)-4-hydroxy-2H-chromen-2-ones2.1.5 Synthesis of Functionalized 2-Hydroxy-3-oxo-2,3-dihydrobenzofuran-2-carboxamides and 2-Hydroxy-3-oxo-2,3-dihydrobenzofuran-2-carboxylates2.1.6 Synthesis of Functionalized 2-Hydroxyphenylated α-Ketoamides2.2 Electrochemical Organic Synthesis2.2.1 Synthesis of 3-Selenylated/Sulfenylated Derivatives of 2-Amino-1,4-naphthoquinones2.2.2 Synthesis of Functionalized 6-(Arylthio/Arylseleno)benzo[a]phenazin-5-ols2.2.3 Synthesis of Functionalized Alkyl 2-Hydroxy-3-oxo-2,3-dihydrobenzofuran-2-carboxylates3 Conclusions
Keywords: photochemistry; visible light; electrochemistry; electrosynthesis; radical mechanistic pathway; green chemistry